Spatial replacement of dung beetles in edge‐affected habitats: biotic homogenization or divergence in fragmented tropical forest landscapes?. Issue 4 (24th January 2016) - Filgueiras, Bruno K. C.; Tabarelli, Marcelo; Leal, Inara R.; Vaz‐de‐Mello, Fernando Z.; Peres, Carlos A.; Iannuzzi, Luciana
Abstract: Aim: In this study, we investigate whether anthropogenic land use and habitat fragmentation lead to a process of either homogenization (decreasing spatial replacement and increasing nestedness) or divergence (increasing spatial replacement and decreasing nestedness) of dung beetle assemblages in edge‐affected habitats. Location: A fragmented landscape of the Atlantic forest of north‐east Brazil. Methods: We investigate the extent to which beta diversity of dung beetle assemblages varies in edge‐affected habitats at different spatial scales (i.e. traps along an interior–exterior nonlinear gradient, within and among habitats). We compare species replacement and nestedness of dung beetle assemblages using (1) multiple dissimilarity measures accounting for compositional heterogeneity across forest (i.e. forest edges, core primary forest areas and small fragments) and matrix habitats (i.e. sugar cane plantations and pastures) and (2) distance matrices accounting for the multivariate structure of dissimilarity. Results: (1) Each habitat supported a distinct dung beetle assemblage; (2) there was a strong influence of anthropogenic land use and fragmentation‐related effects on dung beetle β‐diversity, with species replacements increasing in edge‐affected and matrix habitats providing support for the divergence hypothesis at all spatial scales; (3) edge effects enhanced species replacement across assemblages; (4) dung beetle assemblages were not randomly distributed, with habitat type leading to a strongly nested pattern of species composition; and (5) both dung beetle replacement and nestedness were not correlated with geographic distance, whereby neighbouring sites were not necessarily more similar in their community composition. Main conclusions: Species replacement is strongly influenced by habitat configuration and β‐diversity increases in edge‐affected habitats. Accordingly, anthropogenic land use and habitat fragmentation clearly promote community‐level taxonomic divergence in human‐modified landscapes. Landscape‐scale divergence likely results from a non‐random distribution of both forest‐dependent and disturbance‐adapted species across all habitats, which are in marked contrast in terms of suitability.